Factors affecting purchase intention of Vietnamese young customers at shopee - Nguyen, Ngoc Diep (H. : ĐHQGHN, 2020)
The paper found E-commerce Knowledge, Perceived Reputation, Perceived Risk, and Perceived Technology to be the most effective components of the Online Trust; and Online Trust are key influencers of online purchase intention.